Autonomous learning materials of structure and written expression for TOEFL preparation - Aung Si Thu (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
The aim of this study was to develop appropriate autonomous learning materials of structure and written expression of TOEFL preparation for autonomous learners for the Centre for Language and Development of Yogyakarta State University based on the learning needs and target needs of the autonomous learners. The research was an educational research and development (RD) adapting ADDIE model (Branch, 2009). Two instruments (questionnaire and test) for needs analysis and two instruments for validation were used. The data from the needs analysis and the material validation were analyzed quantitatively through descriptive statistics. The research findings revealed that the autonomous learning materials were appropriate in terms of input, learning activities, layout, design and organization. The learners’ role is to learn the materials individually and teacher's role is to be a guide and cooperator. All of the learning activities include reading of explanations of forms and functions, doing practices for forms and functions, multiple choice, and doing reflection. Every unit has the following organizing unit title, instructions for learners, grammatical form and functions, activities of forms, functions, and TOEFL tests items, online activities for further learning, learning essentials, reflection, self-test (TOEFL) and answer keys.